MAA101 - Calculus for Science Students 1 February 2021 - PPSM, Pusat Pengajian Sains Matematik (Universiti Sains Malaysia, 2021)
Please check that this examination paper consists of FIVE (5) pages of printed material before you begin the examination. Instructions: Answer FOUR (4) questions.